Introduction to KNOWLEDGE-THAT/KNOWLEDGE-HOW: BETWEEN PHENOMENOLOGY AND ANALYTIC PHILOSOPHY – Thematic Dossier - LUDUŞAN, Adrian; RUSU, Mihai (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
The ongoing debate surrounding know-how and skill is one of the most animated and diverse areas of contemporary philosophy. In fact, the inquiry is hardly limited to philosophical theories and arguments, as inputs from cognitive psychology and neuroscience, linguistics, computer science, and other fields have been regularly called upon and analyzed in the literature. Moreover, the range of philosophical theories and traditions that have been brought to bear on the debate is unusually vast, stretching from the ancient to the most novel, and from classical analytic philosophy to various strands of continental philosophy, of which the phenomenological tradition has probably been appealed to the most, whether to lend support to, or to criticize a certain idea.